PENGARUH KUALITAS SISTEM, KOMPLEKSITAS PENGGUNAAN, DAN KESIAPAN TEKNOLOGI INFORMASI TERHADAP MINAT WAJIB PAJAK ORANG PRIBADI DALAM MENGGUNAKAN E-FILING (STUDI KASUS PADA KPP PRATAMA BUKITTINGGI) - Ika Nanda Amalia; Tartila Devy (Jurnal Ekonomi dan Bisnis, 2024)
E-Filing interest among individual taxpayers at KPP Pratama Bukittinggi, either partially or simultaneously, is the target of this research, which seeks to analyse the impact of system quality, usability, and IT preparedness. Quantitative techniques utilising a descriptive explanatory research strategy are employed in this study. Primary data collected for this study came from surveys sent out via mail or online using Google Forms. One hundred individuals who were eligible to participate that is, taxpayers with an account at KPP Pratama Bukittinggi and experience with electronic filing were chosen for the survey through a purposive sampling procedure. This study employed IBM SPSS Statistics version 24 for its data analysis. The study found that while system quality has a positive and statistically significant effect on taxpayers' interest in e-Filing, the complexity of the system has a negative and statistically significant effect on taxpayers' interest in using it for required purposes. taxpayers' interest in utilising e-Filing is positively and significantly impacted by their level of information technology readiness. Individual taxpayers' interest in utilising e-Filing is positively and significantly impacted by system quality, complexity of usage, and information technology readiness all at once.